The Economics of Security Analysis - Hou, Kewei; Mo, Haitao; Xue, Chen; Zhang, Lu (Management Science, 2024)
The investment capital asset pricing model, in which expected returns vary cross-sectionally with investment, profitability, and expected growth, provides an equilibrium foundation for Graham and Dodd’s security analysis. The q 5 model is a good start to explaining prominent security analysis strategies, such as Abarbanell and Bushee’s fundamental signals, Frankel and Lee’s intrinsic to market, Greenblatt’s “magic formula,” Asness et al.’s quality minus junk, Bartram and Grinblatt’s agnostic analysis, operating cash flow to market, and Penman and Zhu’s expected-return strategy as well as best performing active discretionary funds, such as Buffett’s Berkshire Hathaway. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The internet appendix and data are available at https://doi.org/10.1287/mnsc.2022.4640 .